(3x+1)=13-6x

Simple and best practice solution for (3x+1)=13-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+1)=13-6x equation:


Simplifying
(3x + 1) = 13 + -6x

Reorder the terms:
(1 + 3x) = 13 + -6x

Remove parenthesis around (1 + 3x)
1 + 3x = 13 + -6x

Solving
1 + 3x = 13 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
1 + 3x + 6x = 13 + -6x + 6x

Combine like terms: 3x + 6x = 9x
1 + 9x = 13 + -6x + 6x

Combine like terms: -6x + 6x = 0
1 + 9x = 13 + 0
1 + 9x = 13

Add '-1' to each side of the equation.
1 + -1 + 9x = 13 + -1

Combine like terms: 1 + -1 = 0
0 + 9x = 13 + -1
9x = 13 + -1

Combine like terms: 13 + -1 = 12
9x = 12

Divide each side by '9'.
x = 1.333333333

Simplifying
x = 1.333333333

See similar equations:

| -3(4x-8)=-12x+24 | | 56=3(a-5)-4a | | 2x+9y=1728 | | x^2-3x-4=-2x^2+2x-2 | | W=FDford | | (2x+3)(2x-3)=4(x+2)(x-2)+2 | | 22x-5-16x+3=19x-6-13x+11 | | x-.23x=474.32 | | x(2+10)+y(9+2)=3488 | | Y=3.2x+44.61 | | 6x-30=21 | | 6x^2-4y-7=0 | | 249=4b+7(-6b+3) | | 8(2x+2)=6 | | 3x+10y=-8 | | 14=8(n-2)-10(1-n) | | x-8x+1=9-10x | | -3.1+1.6x=0.86 | | 3(2a-2)=24 | | 12x+11y=3488 | | 2x-4+3=75 | | 2(-4y+6z-1)+2z=-7 | | .3m=4 | | D(3D-7)=0 | | 10x+8=8.1 | | 3(3x+1)=13-6 | | y+(y+5)+2y=57 | | -3.1+1.6=-0.86 | | x^2+34x-367=0 | | 4+5x=10+2x | | e^5t+1=0 | | 13=5-(4m+2) |

Equations solver categories